THE COMPONENTS ECONOMIC SUBSTANCE OF THE SYSTEMS MAINTENANCE AND REPAIRS OF FIXED ASSETS OF REGIONAL GAS SUPPLY SYSTEM - Korol, H. O.; Trush, Yu. T. (Science and Transport Progress, 2008)
The components of system of service and repairs of main means of regional gas supply system are determined, assets, their terminology according to interbranch and branch standards is specified.